1993
DOI: 10.2527/1993.7192365x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for carcass traits estimated from Angus field records

Abstract: The American Angus Association has sponsored a carcass evaluation since 1974. The carcass data collected as a part of this program are used by the association to conduct a biannual sire evaluation for carcass merit. This paper presents age-adjustment factors and genetic parameter estimates for carcass traits to be used in the Angus carcass genetic evaluation program. Because of the large range in slaughter ages, age classes were defined as all those animals slaughtered at an age of < or = 480 d and those with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
45
5
7

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 8 publications
24
45
5
7
Order By: Relevance
“…Koots et al (1994b) reported a mean genetic correlation of 0.38 between HCW and FAT, which was similar in sign but larger in magnitude than in the present study. Similarly, positive and small to moderate genetic correlations between HCW and FAT have been reported with Angus field data (0.38, Wilson et al 1992) and experimental crossbred data (0.13, Crews and Kemp 1999). Although the point estimate for the correlation between direct genetic effects of HCW with MAR was negative (-0.21 ± 0.09), this correlation would not be considered antagonistic because the method for assigning MAR to carcasses resulted in carcasses with higher degrees of marbling receiving lower marbling scores.…”
Section: Multivariate Carcass Trait Heritability and Correlationssupporting
confidence: 71%
See 4 more Smart Citations
“…Koots et al (1994b) reported a mean genetic correlation of 0.38 between HCW and FAT, which was similar in sign but larger in magnitude than in the present study. Similarly, positive and small to moderate genetic correlations between HCW and FAT have been reported with Angus field data (0.38, Wilson et al 1992) and experimental crossbred data (0.13, Crews and Kemp 1999). Although the point estimate for the correlation between direct genetic effects of HCW with MAR was negative (-0.21 ± 0.09), this correlation would not be considered antagonistic because the method for assigning MAR to carcasses resulted in carcasses with higher degrees of marbling receiving lower marbling scores.…”
Section: Multivariate Carcass Trait Heritability and Correlationssupporting
confidence: 71%
“…Heritability estimates generally compared favorably with those summarized by Koots et al (1994a), where weighted average heritabilities were equal to or greater than those of the present study with the exception of HCW, which was higher here than in that summary (0.23). The moderate heritability for HCW in the present study compares more favorably to the estimate of 0.31 reported by Wilson et al (1992) using Angus field data, but was lower than the estimates of 0.48 and 0.61 by Benyshek (1981) and Meyer et al (2004), respectively, using Hereford field data. Experimental data from the Meat Animal Research Center in Nebraska yielded HCW heritability estimates of greater than 0.44 in three studies (MacNeil et al 1984;Splan et al 1998Splan et al , 2002.…”
Section: Single Trait Variance Components and Genetic Parameterssupporting
confidence: 49%
See 3 more Smart Citations